The Correlation Between Teacher’s Strategies and Reading Comprehension Achievement of the Tenth Grade Students of SMKN 4 Pangkalpinang 2020/2021 - Sugiarto, Dody; Nur Imani, Hena Oktaliana (EEdJ: English Education Journal, 2022)
The objective of this study was to find out the teacher’s strategies, the personality differences between male and female students, the students’ reading achievement, and the correlation between students' personality and their achievement in reading at the tenth grade students of SMKN 4 Pangkalpinang. Furthermore, the limitation of this study were 1) the purpose of reading focused on reading to search for simple information, reading to learn from texts, and reading for general comprehension, 2) type of reading was intensive reading, extensive reading. The research method used was quantitative with a correlational design. The population of this study was 2 classes consisting of 33 students at the tenth grade of SMKN 4 Pangkalpin ang. The data were analyzed by using Pearson Product-Moment Correlation. The result showed that the ????????????(0.945) was higher compared to ???????????????????????? at significant level 5% (0.344). Thus, the alternative hypothesis (????????) was accepted and null hypothesis (????????) was rejected. Furthermore, there was a significant correlation between teacher’s strategies and their achievement in reading. In conclusion, teacher’s strategies influenced their achievement in reading.